2020
DOI: 10.2174/1874210602014010196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Expression of Periodontal Markers in Dental and Bone Marrow-derived Mesenchymal Stem Cells.

Abstract: Background: Periodontal ligament stem cells are a source of mesenchymal stem cells, but it is unclear whether their phenotype is distinct from mesenchymal stem cells derived from different tissues, such as those derived from bone marrow. Objective: To investigate the expression of the putative PDL markers asporin, periostin, nestin and cementum protein 1, by periodontal ligament stem cells both constitutively and during osteogenic differentiation when compared to bone marrow-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Interestingly, the decellularization process did not affect the expression of these proteins, which is in accordance with previous works. , Type I collagen and FIB are two of the predominant proteins present in the native PDL tissue . In fact, previous studies have already reported that COL I, FIB, and LAM are the main ECM proteins present in cell-derived ECM from various sources. , ASP is an ECM protein, also known as PDL-associated protein 1 (PLAP1), and is predominantly expressed in the PDL. , Interestingly, PDLSCs expressed proteins typically present in bone such as OPN and OC. These two proteins are present in the cementum and alveolar bone .…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the decellularization process did not affect the expression of these proteins, which is in accordance with previous works. , Type I collagen and FIB are two of the predominant proteins present in the native PDL tissue . In fact, previous studies have already reported that COL I, FIB, and LAM are the main ECM proteins present in cell-derived ECM from various sources. , ASP is an ECM protein, also known as PDL-associated protein 1 (PLAP1), and is predominantly expressed in the PDL. , Interestingly, PDLSCs expressed proteins typically present in bone such as OPN and OC. These two proteins are present in the cementum and alveolar bone .…”
Section: Discussionsupporting
confidence: 90%
“…PLAP1 and POSTN are major extracellular proteins in PDL tissue 32 and OPG is secreted from human PDL cells to regulate osteoclasts in PDL tissue 33 ; therefore, these proteins (and the genes that encode them) are regarded as PDL-related markers. A previous report revealed that human PDLSCs expressed high levels of PLAP1 and POSTN; however, the expression levels of these genes were extremely low in human osteoblasts 34 , suggesting that line 1-17 cells exposed to D-WMTA and Na-WMTA differentiated into osteoblast-like cells. Furthermore, line 1-17 cells cultured with Na-WMTA expressed lower levels of BMP2, OPN, and ALP genes, compared with cells cultured with D-WMTA.…”
Section: Discussionmentioning
confidence: 88%
“…Asporin is an ECM protein, also known as PDL-associated protein 1 (PLAP1) and is predominantly expressed in the PDL [35,36]. Interestingly, PDLSCs expressed proteins typically present in bone, such as osteopontin and osteocalcin.…”
Section: Discussionmentioning
confidence: 99%